3D Ti/TiO2 current collector for stable zinc metal anode - Ong, Wen Qing (Nanyang Technological University, 2021)
In recent years, Zinc-ion aqueous batteries (ZIABs) have gained significance in popularity as an alternative to Lithium-ion batteries (LIBs) due to their ease of accessibility, cost efficiency compared to Lithium, safety aspects, and environmental friendliness. However, despite many favourable advantages, ZIABs still face challenges, particularly in the formation of dendrites on the Zn anode surface, which limits the electrochemical performance and cycle stability of ZIABs. In this Final Year Project (FYP), a 3D Ti/TiO2 nanotube current collector coupled with Zn anode (Zn@3D Ti/TiO2) was fabricated to ensure uniform Zn2+ ions diffusion such that there will be a homogenous Zn2+ ions plating and stripping reaction during the charging and discharging process. Material characterization tests were carried out to evaluate the morphology, crystallinity well as elemental analysis of the fabricated 3D Ti/TiO2 nanotubes and synthesized Zn@3D Ti/TiO2 electrode. Next, electrochemical characterization tests were carried out in symmetric coin batteries and full cell coin batteries. The Zn@3D Ti/TiO2 | | Zn@3D Ti/TiO2 symmetric coin batteries cell was evaluated against bare Zn || Zn symmetric coin batteries cells which was revealed to have satisfactory cycle stability. Lastly, the electrochemical performance of Zn@3D Ti/TiO2 || CNT@MnO2 full cell coin batteries were evaluated against bare Zn || MnO2 full cell coin batteries. From the result, the fabricated full cell coin batteries had a higher specific capacity over a longer cycle period with higher cycle stability as compared to bare Zn || MnO2 full cell coin batteries. Hence, the issue of capacity fading caused by Zn dendrites due to inhomogeneous Zn2+ ions was better controlled. In conclusion, the proposed strategy showed improvement of the cycle stability of ZIABs by ensuring uniform Zn2+ ions diffusion to achieve homogenous Zn2+ ions plating and stripping reaction during the charging and discharging process.